Nasal fluid release of eotaxin‐3 and eotaxin‐2 in persistent sinonasal eosinophilic inflammation. Issue 8 (2nd July 2014) - De Corso, Eugenio; Baroni, Silvia; Battista, Mariapina; Romanello, Matteo; Penitente, Romina; Di Nardo, Walter; Passali, Giulio Cesare; Sergi, Bruno; Fetoni, Anna Rita; Bussu, Francesco; Zuppi, Cecilia; Paludetti, Gaetano
<x xml:space="preserve">Abstract</x> Background The aim of the present study was to measure eotaxin‐3 (CCL26) and eotaxin‐2 (CCL24) in nasal lavage fluid of patients with different forms of chronic sinonasal eosinophilic inflammation to evaluate their role in the pathophysiology of nasal hypereosinophilia. Methods The study was an analytic cross‐section study, level of evidence 3b. Patients (n = 80) with nasal hypereosinophilia were randomly recruited and grouped in the following categories: persistent allergic rhinitis (AR) (n = 25), nonallergic rhinitis with eosinophilia syndrome (NARES) (n = 30), and chronic rhinosinusitis with polyps (CRSwNP) (n = 25). Non‐rhinitic volunteers (n = 20) were recruited as controls. CCL24 and CCL26 concentrations were measured by enzyme‐linked immunosorbent assay (ELISA) Quantikine Human Immunoassays (R&D Systems, Minneapolis, MN) in nasal lavage fluids. Differential cell counts were performed by microscopic cytological examination of nasal tissue scraped from the inferior turbinate. Results Mean CCL26 levels were significantly higher (p < 0.05) in AR and in NARES (132.0 pg/mL and 187.63 pg/mL, respectively) than in the control group (13.5 pg/mL); in patients with CRSwNP, CCL26 values were increased compared to controls even though the difference was not statistically significant (58.9 pg/mL vs 16.5 pg/mL). Mean CCL24 levels measured in AR, NARES, and CRSwNP were significantly increased (p < 0.05) compared to controls (96.7 pg/mL, 135.4 pg/mL, and 107.0 pg/mL, respectively, vs 32.2 pg/mL). Moreover, we observed a significant correlation between CCL24 and CCL26 levels, evaluating them intraindividually by Spearman's rank correlation test. Finally, a significant correlation was found between CCL24 and CCL26 levels and the percentage of eosinophilic infiltration of nasal mucosa. Conclusion Our data suggest that CCL26 and CCL24 are likely involved in the pathogenesis of chronic nasal hypereosinophilia, with a complex cooperation and different involvement of the various members of eotaxin family. Further studies are necessary to better understand the actual physiopathologic mechanism, possible clinical relevance, and therapeutic implications.